5x-3(2x+7)x=-2

Simple and best practice solution for 5x-3(2x+7)x=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3(2x+7)x=-2 equation:



5x-3(2x+7)x=-2
We move all terms to the left:
5x-3(2x+7)x-(-2)=0
We add all the numbers together, and all the variables
5x-3(2x+7)x+2=0
We multiply parentheses
-6x^2+5x-21x+2=0
We add all the numbers together, and all the variables
-6x^2-16x+2=0
a = -6; b = -16; c = +2;
Δ = b2-4ac
Δ = -162-4·(-6)·2
Δ = 304
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{304}=\sqrt{16*19}=\sqrt{16}*\sqrt{19}=4\sqrt{19}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-16)-4\sqrt{19}}{2*-6}=\frac{16-4\sqrt{19}}{-12} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-16)+4\sqrt{19}}{2*-6}=\frac{16+4\sqrt{19}}{-12} $

See similar equations:

| 1/2x+17=37 | | x÷14=6 | | 2x=(6x+2) | | 5.4.x=3.4(8+x) | | 3x-5+4x-14=180 | | 2x+45=120 | | 119+(3x+4)=180 | | 2(x+5)+7=23 | | 1/3+2/5f+3/4=21/12 | | X+10°+x=180° | | 2x+24=11x-86 | | (43x+8)/(4x+27)=5 | | -8=-6x+4(x+2) | | 5x+26=6x+9 | | X*2+8x+16=3 | | 2^(x-6)=6 | | (3x+2)+(34+x)=180 | | 2^x-6=6 | | 4x+(2+4x)=90 | | s-1.8*15=6 | | 2x+10=1x+45 | | 2g-2g+-17g—18=-16 | | 110/55=x/100 | | 17=n×50 | | X/100=x/100 | | 9(p-2)=6p+3 | | n×20=14 | | 110/100=x/55 | | v/23=16 | | 31=4(x-8)-9 | | (x+x)+(x+x)=96 | | 23x+113=120 |

Equations solver categories